Measurement of Surface Velocity in a 150 mm × 1270 mm Slab Continuous-Casting Mold - Yang Wang (Metals, 2020)
Surface velocity in the continuous-casting mold needs to be studied to better control the quality of steel products. In this paper, the measurement of surface velocity in a 150 mm × 1270 mm slab continuous-casting mold was investigated. Taking the slag layer into consideration, a numerical simulation was performed which was validated by a particle image velocimetry test. A nail-board experiment was also conducted to measure surface velocity in the continuous-casting mold. The effect of nail diameter used in nail-board experiment on the measurement of the surface velocity was also discussed to improve the precision of nail-board experiment result. The results showed that the maximum surface velocity was 0.739 m/s around the mid-section of the free surface, and the results of nail-board experiments were more accurate when the steel nail diameter was 10 mm.